Fecundity, Food and Feeding Habits and Growth Pattern of Galeoides Decadactylus in Nigeria Coastal Waters - M.O, Ezekiel; A.O, Olusola; Bernard, Edah; U.C, Udoezika (International Journal of Natural Sciences Research, 2013)
Twenty five (25) Galeoides decadactylus bought from Ijora were examined for the growth pattern, food and feeding habit and reproduction biology of the fish. The standard length of the specimen ranged from 17.5 to 21.7. The correlation coefficient was 0.85 which showed a strong correlation between the standard length and weight. Out of the twenty five fish specimens 20% has empty stomach. The condition factor ranged from 2.30 to 2.89 for the combined sexes. The result from chi-square test showed that the number of female is more significant than the number of males.